The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.52380/ijpes.2022.9.1.521
|View full text |Cite
|
Sign up to set email alerts
|

Successful Aging Scale: Validity and Reliability Study

Abstract: The purpose of this research is to develop a successful aging scale specific to Turkey. This research was carried out on two different study groups for exploratory and confirmatory factor analysis studies. The study group formed for exploratory factor analysis consists of 521, and the group for confirmatory factor analysis consists of 243 elderly individuals.By the analyzes carried out, the KMO value of the Successful Aging Scale was found to be .97; validity and reliability analyzes were continued. It was obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
(20 reference statements)
1
7
0
Order By: Relevance
“…In our study, female participants had a higher dependency ratio on their children than male participants, which is not surprising given that females were encouraged to stay at home and take sole responsibility for domestic affairs and child care [2]. After examine the previous studies, it is seen that huge different in terms of demographic values conducted for active aging [19], [22], [32].…”
Section: Discussion/ Conclusionmentioning
confidence: 73%
See 4 more Smart Citations
“…In our study, female participants had a higher dependency ratio on their children than male participants, which is not surprising given that females were encouraged to stay at home and take sole responsibility for domestic affairs and child care [2]. After examine the previous studies, it is seen that huge different in terms of demographic values conducted for active aging [19], [22], [32].…”
Section: Discussion/ Conclusionmentioning
confidence: 73%
“…Data adequacy: KMO and the Bartlett test of Sphericity ratio is > 0.5 for the data set to be considered suitable for further factor analysis [19]. The research revealed that the KMO coe cient was.0.701.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations